Coastal Landform and Its Indicative Risk of Changes Through Integrated Satellite and on Ground Observations for Coastal Development and Revitalisation In Pati, Central Java - Tubagus Solihuddin; Hadiwijaya Lesmana Salim; Eva Mustikasari; Aida Heriati (Jurnal Segara, 2019)
An appropriate foreshore management should take into account coastal processes based on physical and biological features of the particular coastal environment. This study aims to determine the coastal landform and its instability and susceptibility through satellite study, thematic map, and groundtruth checking. The coastal landform of Pati is typified by the muddy coast with ~1 km tidal mudflat moving seaward and coastal plain moving landward. Mangrove ecosystem, mainly Avicennia, intermittently occurs along the coast of Pati resting on muddy substrates where tributaries drain off water from the hinterland. The coastal plain is largely occupied by salt and/or fish ponds. Considering the geological condition, coastal characteristic, and oceanographic processes, the coast of Pati has medium to high-risk level of landform changes with shoreline changes greater than 1 m/yr and 5 to 10 yearly coastal inundation driven by the erosion and sedimentation. The study provides insight in recognising time and space scale of an indicative risk of landform changes and its driving processes for the coastal management and planning purposes.